2021
DOI: 10.1099/jgv.0.001524
|View full text |Cite
|
Sign up to set email alerts
|

Tobamoviruses of two new species trigger resistance in pepper plants harbouring functional L alleles

Abstract: Tobamoviruses are often referred to as the most notorious viral pathogens of pepper crops. These viruses are not transmitted by invertebrate vectors, but rather by physical contact and seeds. In this study, pepper plants displaying mild mottle and mosaic symptoms were sampled in four different regions of Peru. Upon double-antibody sandwich enzyme-linked immunosorbent assay (DAS-ELISA) tests, seven samples cross-reacted weakly with antibodies against pepper mild mottle virus (PMMoV), suggesting the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…We additionally tested the same four samples with degenerate potyvirus (Gibbs & Mackenzie, New Dis Rep. 2022;46:e12120. wileyonlinelibrary.com/journal/ndr2 1 of 2 https://doi.org/10.1002/ndr2.12120 F I G U R E 2 Chlorosis observed on calibrachoa cuttings infected with Chili pepper mild mottle virus 1997) and orthotospovirus (Chu et al, 2001) primers; no amplicons were observed.CPMMoV was first reported in 2021 from field-grown pepper in Peru(Vélez-Olmedo et al, 2021). To the best of our knowledge, this is the first report of CPMMoV in calibrachoa or any other greenhousegrown ornamental host.…”
mentioning
confidence: 68%
See 3 more Smart Citations
“…We additionally tested the same four samples with degenerate potyvirus (Gibbs & Mackenzie, New Dis Rep. 2022;46:e12120. wileyonlinelibrary.com/journal/ndr2 1 of 2 https://doi.org/10.1002/ndr2.12120 F I G U R E 2 Chlorosis observed on calibrachoa cuttings infected with Chili pepper mild mottle virus 1997) and orthotospovirus (Chu et al, 2001) primers; no amplicons were observed.CPMMoV was first reported in 2021 from field-grown pepper in Peru(Vélez-Olmedo et al, 2021). To the best of our knowledge, this is the first report of CPMMoV in calibrachoa or any other greenhousegrown ornamental host.…”
mentioning
confidence: 68%
“…ON381946‐ON381953) and those from each primer set shared 99–100% nucleotide identity with each other, and 99–100% nucleotide identity with the corresponding regions of CPMMoV isolate Oxampampa4 (MN164455) confirming the presence of this tobamovirus. CPMMoV‐specific CP gene primers (Vélez‐Olmedo et al., 2021) also produced amplicons of the expected size, c. 1,100 bp. No other tobamovirus sequences were detected with any of these primer sets.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…These results show that the virus population at NLL is highly heterogeneous in terms of resistance‐breaking phenotypes. PMMoV isolates of P 1 and P 0 pathotypes have never been reported from nature, which suggest that mutations towards lower, not only higher, pathotype may have important fitness costs, so that PMMoV genotypes of P 1 and P 0 pathotypes would be outcompeted by P 0 and P 1 genotypes of other tobamovirus species commonly found in pepper crops (Fraile et al, 2011 ; Moury & Verdin, 2012 ; Vélez‐Olmedo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%